Exploring the customer experiences in Bosphorus Zoo - (:unkn) unknown (My University, 2010)
The main purpose of this study is to explore current and possible customer experiences in Bosphorus Zoo. Since there is no previous research conducted on Turkish zoos' customer experiences, we conduct an exploratory research taking the form of depth interviews. Then, we group the experiences according to strategic experiential modules (sense, feel, think, act and relate).
Keywords: Customer experience; Experiential marketing; Services marketing